Comparative Analysis of Risk, Profitability, Market Ratios and Asset Selection in Tesla, Apple, and Exxon Mobils - Zhang, Chenxi (Transactions on Economics, Business and Management Research, 2024)
Asset allocation is a fundamental aspect of attaining financial growth and stability. This study explores three major companies: Tesla, Apple, and Exxon Mobil—competitors in the automotive, technology, and energy sectors consecutively. From the point of view of investing in the companies, the study provides a discussion on various financial indicators (beta, debt ratio, profit margins, market to book ratio) to understand what investors may pay attention to in choosing the most suitable companies to invest. It is found that Tesla, given that it has a high beta and a potential for growth, is more appealing for growth and momentum investors who are more inclined to take risks to get better rewards. In the meantime, Exxon Mobil, as a not very high-risk company, still provides consistent profits for growth and income investors who look for reliable dividends through the entire period. Apple is a popular choice for investors who seek positive earnings, innovation, and market dominance because investors across the board, including those looking out for PEG ratio and DCF (Discounted Cash Flow) analysis, are attracted by these imperatives. Thus, the paper generates valuable guidance to the shaping of investment strategies to correspond with particular financial situations and firm kinds.